Nationwide epidemiologic survey of Kawasaki disease in Japan, 2015–2016. Issue 4 (16th April 2019) - Makino, Nobuko; Nakamura, Yosikazu; Yashiro, Mayumi; Kosami, Koki; Matsubara, Yuri; Ae, Ryusuke; Aoyama, Yasuko; Yanagawa, Hiroshi
Abstract: Background: Approximately 50 years have passed since Kawasaki disease (KD) was first reported. The KD nationwide survey began in 1970. Although >360 000 cases have already been reported in Japan, the cause is still unknown. In Japan, the number of patients and incidence rate of KD has continued to increase. It is necessary to examine the trend of the occurrence in the surveillance of KD. Methods: The nationwide survey of patient incidence in 2015 and 2016 was conducted in 2017, as the 24th nationwide survey of KD. A questionnaire was sent to pediatric departments in hospitals with >100 beds and specialized pediatric hospitals, and was responded to by the attending pediatricians. Results: The total number of patients in 2 years was 31 595, and the sex ratio (male/female) was 1.34. The incidence rate (/100 000 children aged 0–4 years/year) was 330.2 (371.2 in boys, 287.3 in girls) in 2015, and 309.0 (343.2 in boys, 273.2 in girls) in 2016. The number of patients by month peaked in January. The age‐specific incidence rate according to sex was highest in children between 9 and 11 months of age, after which the incidence rate gradually decreased with advancing age. Conclusions: We summarize the most recent nationwide survey of KD and consider the change in the epidemiologic picture.